Screening HIV-associated neurocognitive disorders (HAND) among HIV positive patients attending antiretroviral therapy in South Wollo, Ethiopia. (February 2017) - Tsegaw, Million; Andargie, Gashaw; Alem, Getnet; Tareke, Minale
Abstract: Background: The vast majority of people living with HIV/AIDS reside in low and middle income countries, particularly in Sub-Saharan Africa, including Ethiopia. Despite the huge number of service users in the local area, cognitive disorder among HIV patients has not been extensively studied and there is a dearth of knowledge on the subject. The objective of this study was to assess the prevalence and associated factors of HIV-associated neurocognitive disorder among people living with HIV/AIDS in antiretroviral therapy (ART) clinics. Methods: Institution based cross sectional study was conducted from April to May, 2015 at Dessie Referral Hospital & Kombolcha Health Center. International HIV Dementia Scale was used to screen HIV associated neurocognitive deficits. Logistic regression analysis was used to assess predictors of neurocognitive disorders. Result: The risk of HIV associated neurocognitive disorder was 36.4%. Those who had CD4 count of 500 cells/dl or less (AOR = 2.368 (1.524, 3.680)), no formal education (AOR = 4.287 (2.619, 7.016)), poor medication adherence (AOR = 1.487 (1.010, 2.180)) and older age (AOR = 3.309 (1.259, 8.701)) were found to be significantly associated with HIV associated neurocognitive disorders. Conclusion: The risk of HIV-associated neurocognitive disorder was found to be high among people living with HIV/AIDS. This emphasizes the need of regular cognitive screening for early identification and appropriate intervention.